Use Of Foreign Experience In Providing Informational Psychological Security Among Youth - Zamira Bakhtiyarovna Bilolova (Euro Asian Journal Publishing, 2024)
This article highlights the importance of using foreign experience in ensuring psychological safety of information among young people, the need to learn to distinguish between the useful and harmful aspects of information and the formation of a culture of information consumption among young people.
Keywords: information psychological safety; culture of information consumption; Internet; Internet safety